Accelerated CSharp 2005 - Nash, Trey (Apress, 2012)
When I joined the Common Language Runtime (CLR) team in 1998, I had no idea what an impact .NET and the CLR would make on the industry. From the very first meeting I attended (about the pros and cons of a garbage-collected environment compared to a referenced-counting model), it was clear that these were huge steps forward for Microsoft. Incidentally, the second meeting I attended was about VB6-style edit-and-continue debugging, and it was not until version 2 of the .NET Framework more than seven years later that we actually realized this particular feature and delivered it to C# as well as VB users. The .NET Framework and C# started out as ambitious projects and have grown and matured appreciably over the years.